Itch! : everything you didn't want to know about what makes you scratch - Sanchez, Anita, 1956- (Houghton Mifflin Harcourt, 2018)
Provides a scientific explanation for the reasons why people itch; describes the animals and plants responsible; and discusses how people have dealt with itching and the impact it has had in history.